Diagnostics of three-shaft turbojet two-circuit engine by using the dynamic parameters - Карпов, Є. М.; Карпов, А. Є. (Proceedings of National Aviation University (archive), 1998)
Given here are the block-dynamic diagram of three-shaft TTCE and the method of determination of basic paramétrés by using throttle and moment characteristics, and approaches to diagnostics of three-shaft turbojet two-circuit engine by dynamic parameters